Answer:
x = 27/16
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define equation
x + 5/9x = 2(3 - x)
Step 2: Solve for x
- Distribute 2: x + 5/9x = 6 - 2x
- Combine like terms: 14/9x = 6 - 2x
- Add 2x on both sides: 32/9x = 6
- Divide 32/9 on both sides: x = 27/16
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 27/16 + 5/9(27/16) = 2(3 - 27/16)
- Multiply: 27/16 + 15/16 = 2(3 - 27/16)
- Subtract: 27/16 + 15/16 = 2(21/16)
- Multiply: 27/16 + 15/16 = 21/8
- Add: 21/8 = 21/8
Here we see that 21/8 does indeed equal 21/8.
∴ x = 27/16 is a solution to the equation.